Supply Chain Management in Digital System Model for Product Management for the Bank in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The objectives of this research are to design supply chain management in digital system model for product management for the bank in Thailand and to evaluate the model. The Samples are ten experts on supply chain. The data is analysed by means and standardized deviations. The research result shows that model consists of eight elements namely main components, Supplier, Manufacture, Distributor. Retailers Customer, Satisfaction. Feedback. supply chain management in digital system model for product management for the bank in Thailand using Black-Box technique method. and the result of the assessment of supply chain management in digital system model for product management for the bankÂ in Thailand is appropriate at the high level ( X = 3.62, S.D. = 0.82 ) . The model can be appropriately applied in actual work settings.Â